Phytochemistry : Volume 3: Marine Sources, Industrial Applications, and Recent Advances - Egbuna, Chukwuebuka; Chinenye Ifemeje, Jonathan; Kumar, Shashank; Sharif, Nadia; Apple Academic Press (Toronto ; New Jersey : Apple Academic Press, 2018)
This volume presents chapters that discuss secondary metabolites of marine origin, the industrial applications of phytochemicals, and recent advances in phytochemical research. It considers production of secondary metabolites and accumulations through in vitro cultures and also reviews the effects of natural products as biopesticides and as eco-friendly corrosion inhibitors. In addition, the volume discusses the effects of the environment on the distribution of phytochemicals and the roles of phytochelatins and heavy metal tolerance in plants.
Part 1: Marine Sources Of Secondary Metabolites -- 1. Phytochemicals of Marine Origin -- Nadia Sharif et al. -- 2. Marine Sponge Alkaloids: A Source of Novel Anticancer Agent -- Musarat Amina and Hanan M. Al-Yousef -- 3. Marine Antioxidants and Assay Methods -- Onyeka Kingsley Nwosu and David Okechukwu Okeke -- 4. Extraction of Marine Phytochemicals: Methods and Techniques -- Nadia Sharif, Neelma Munir, and Shagufta Naz -- Part 2: Industrial And Medicinal Applications Of Phytochemicals -- 5. Biotechnology Approach to the Production of Phytochemicals: An Introduction -- Hameed Shah et al. -- 6. Secondary Metabolites Accumulation and Production through In Vitro Cultures -- Hussien M. Daffalla and Azza Migdam Elsheikh -- 7. Practical Processes Involved in the Production of Phytochemicals by Plant Tissue Culture -- Hanan M. Al-Yousef -- 8. Medicinal and Industrial Applications of Bromelain -- Ramesh Kumar and Abhay K. Pandey -- 9. Cysteine Proteases from Plants and Its Applications -- Juan Abreu Payrol et al. -- 10. Phytotherapy and Encapsulation -- aban Keskin, Merve Keskin, and Sevgi Kolayl -- 11. Effective Processing Methods for Fruits and Vegetables -- Maria Aslam, Sidra Khalid, and Hafsa Kamran -- Part 3: Environmental Concerns And Eco-Friendly Control Measures -- 12. Effects of Environmental Factors on the Accumulation of Phytochemicals in Plants Sechene -- Stanley Gololo -- 13. Effects of Environment on the Chemical Constituents and Biological Characteristics of Some Medicinal Plants -- Vinesh Kumar and Yogita Sharma -- 14. Phytochelatins and Heavy Metal Tolerance in Plants -- Maria Catherine B. Otero and Genevieve D. Tupas -- 15. Phytochemical Biopesticides -- Olumayowa Vincent Oriyomi -- 16. Sustainable Approach in Integrated Pest Management: Role of Phytomolecules as Biopesticide -- Rakesh Kumar Gupta, Prem Prakash Kushwaha, and Shashank Kumar -- 17. Essential Oil in Pest Control and Disease Management -- Arvind Saroj et al. -- 18. Inhibition of Mild Steel Corrosion in Acidic Media by Phytochemicals -- Basu Maan Daas -- Part 4: Recent Advances -- 19. Novel Terpenoids as Anticancer Stem Cell Agents -- Rebati Malik et al. -- 20. Evaluation of the Phytohemagglutinin Activities of Echinacea Species in Ontogenesis -- Sergey V. Pospelov.
Includes bibliographical references and index.
Also available in print format.
Keywords: MEDICAL / Alternative Medicine; MEDICAL / Pharmacology; Phytochemicals; Drugs -- Research; Electronic books